2015
DOI: 10.1002/ptr.5320
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Effect of Galbanic Acid via Activation of Caspases and Inhibition of Mcl‐1 in H460 Non‐Small Lung Carcinoma Cells

Abstract: Galbanic acid (GBA), a major compound of Ferula assafoetida, was known to have cytotoxic, anti-angiogenic and apoptotic effects in prostate cancer and murine Lewis lung cancer cells; the underling apoptotic mechanism of GBA still remains unclear so far. Thus, in the present study, the apoptotic mechanism of GBA was investigated mainly in H460 non-small cell lung carcinoma (NSCLC) cells because H460 cells were most susceptible to GBA than A549, PC-9 and HCC827 NSCLC cells. Galbanic acid showed cytotoxicity in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Our understanding of the importance of autophagy and apoptosis in the development and prevention of human disease has improved. In addition, the association between the two has been investigated ( 21 ). Notably, it has been observed that apoptosis-regulating genes, such as Bcl-2 family members (Bcl-2 and CASP9) can also regulate autophagy ( 22 ), while autophagy-associated proteins, such as Atg5, beclin 1 and Atg4D, are also involved in cell apoptosis ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the importance of autophagy and apoptosis in the development and prevention of human disease has improved. In addition, the association between the two has been investigated ( 21 ). Notably, it has been observed that apoptosis-regulating genes, such as Bcl-2 family members (Bcl-2 and CASP9) can also regulate autophagy ( 22 ), while autophagy-associated proteins, such as Atg5, beclin 1 and Atg4D, are also involved in cell apoptosis ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The H460 is a wild-type lung cancer cell without L858R point mutation. 39,40 We used the pure buffer solution and the genomic DNA without any targets as the control group. As shown in Fig.…”
Section: Real Sample Analysismentioning
confidence: 99%
“…Caspase-3 activity appears to regulate the speed of this response. The study of caspase-3 -/-and caspase-9 -/-mice suggested the caspase pathway used for disassembly is cell type specific (20)(21)(22). Our findings suggest that control of HO-1 expression contributes to this process.…”
Section: Discussionmentioning
confidence: 60%